Proposed Hybrid Power Optimization for Wind Turbine/Battery System - Belaid, Saloua; Rekioua, Djamila; Oubelaid, Adel; Ziane, Djamel; Rekioua, Toufik (Periodica polytechnica. Electrical engineering and computer science, 2022)
This paper contributes to the feasibility of a wind turbine/battery system with a hybrid power optimization controller. The proposed method is based on a mathematical optimization approach and allows to achieve an efficient operation of the maximum power point tracking (MPPT) algorithms to obtain an optimal performance level of the wind system and a minimal stress on the battery storage. The different powers have been controlled by a power management control (PMC) method. The objectives of the PMC based are, in first part to satisfy the load power demand and in second part to maintain the state of charge of the battery bank to prevent blackout and to extend the batteries life. A measurement of wind speeds was made during a whole day using a data acquisition system at the laboratory. Also, the different wind turbine parameters were identified at the same Laboratory. All these parameters have been used in simulation models in order to obtain the most realistic mathematical models that are close to the experiment. Real time simulation is performed using RT LAB simulator and the obtained results were matching those obtained in numerical simulation using Matlab/Simulink. The obtained results under two different wind speed profile, with the different comparisons are presented to show the feasibility and the improvement of the proposed study in terms of power, efficiency, time response and effect on battery state of charge under two different wind speeds profile.